Media Pop-Up Book Digital Materi Sistem Peredaran Darah untuk Meningkatkan Hasil Belajar Siswa Kelas V - Diva Aulia Rahmah; Karimatus Saidah; Frans Aditia Wiguna (YASIN, 2026)
Although digital instructional media have been widely developed for various subjects in elementary schools, the development of a Digital Pop-Up Book specifically containing material on the human circulatory system and evaluated in terms of validity, practicality, and effectiveness remains limited. This study aims to develop and analyze the validity, practicality, and effectiveness of Digital Pop-Up Book media on the human circulatory system for fifth-grade elementary school students. The study employed a quantitative approach using the Research and Development (R&D) method and the ADDIE model, which comprises the Analysis, Design, Development, Implementation, and Evaluation stages. The study involved 21 fifth-grade students at SDN Bandar Lor 3, Kediri City, one fifth-grade teacher, and media and subject-matter expert validators. Data were collected through observations, interviews, validation questionnaires, teacher and student response questionnaires, and learning outcome tests in the form of a pre-test and post-test. Validity and practicality data were analyzed using quantitative descriptive analysis, whereas the effectiveness of the media was analyzed using the Wilcoxon Signed-Rank Test with the assistance of SPSS version 25. The findings indicate that the Digital Pop-Up Book media achieved a validity level of 97%, placing it in the highly valid category. The practicality level reached 98% based on teacher responses and 98.7% based on student responses, both of which were classified as highly practical. The Wilcoxon test yielded a significance value of 0.000 < 0.05, indicating that the use of the media was effective in improving students’ learning outcomes. This study confirms that Digital Pop-Up Book media is suitable for use in teaching the human circulatory system. These findings contribute to the development of interactive digital instructional media in Natural and Social Sciences learning and provide practical guidance for teachers in presenting abstract material in a more engaging, concrete, and interactive manner.